Efforts Undertaken by Several ASEAN Countries to Address Childhood and Adolescent Obesity in School-Based Programs: A Systematic Review: Upaya yang Dilakukan Beberapa Negara ASEAN untuk Mengatasi Obesitas Anak dan Remaja dalam Program Berbasis Sekolah: Tinjauan Sistematis - Rahmani, Alinda; Nadhiroh, Siti Rahayu (Universitas Airlangga, 2024)
Background: Childhood and adolescent obesity is on the rise in Southeast Asia. Necessitating stronger actions from ASEAN governments to address this issue, because the significant financial and social welfare implications. Schools provide an effective platform for targeted interventions among children and adolescent groups. Objectives: This study provides an overview of school-based nutrition interventions implemented in ASEAN countries to address childhood and adolescent obesity. Methods: A literature review was conducted by searching multiple databases (Google Scholar, PubMed, ProQuest, ScienceDirect, and Web of Science) between April 1 and May 1, 2023. The search included computer-based searches and manual search in relevant journals. The articles considered were limited to publications from the past 10 years. Discussion: School-based nutrition interventions in ASEAN countries require further development, with attention to key factors such as intervention duration, sample size, and family involvement. Conclusions: Urgent large-scale research is needed to evaluate the effectiveness of existing school-based nutrition programs. Integrated and effective programs require support and collaboration from families, the private sector, and the government.